Binary cations minimize energy loss in the wide-band-gap perovskite toward efficient all-perovskite tandem solar cells - Zhang, Kaicheng; Liu, Chao; Peng, Zijian; Li, Chaohui; Tian, Jingjing; Li, Canru; García Cerrillo, José; Dong, Lirong; Streller, Fabian; Späth, Andreas; Musiienko, Artem; Englhard, Jonas; et al. (Joule, 2024)
Perovskite-based tandem solar cells stand at the forefront of photovoltaic innovation due to their exceptional performance and cost-effective fabrication. This study focuses on minimizing energy losses within a 1.80 eV perovskite sub-cell. We demonstrate that the surface treatment of perovskite with binary guanidinium bromide and 4-fluorophenylammonium iodide synergistically reduces defect densities and adjusts interfacial energy-level alignment. The enhanced passivation effect and the formation of a surface dipole significantly reduce nonradiative recombination and transport losses, leading to a notable increase in the open-circuit voltage and fill factor product, thereby achieving an impressive power conversion efficiency (PCE) of 19.0%. The reproducibility of these findings is confirmed by consistent results across different laboratories. Furthermore, integration with a narrow-band-gap perovskite yields an all-perovskite tandem device with a PCE of 27.2%. This comprehensive understanding of the pivotal role of spacer cations in surface treatment significantly advances the pathway toward efficient perovskite photovoltaics.
CRIS-Team Scopus Importer:2024-08-30
Keywords: 2D phases; all-perovskite tandem solar cell; energy loss; energy-level alignment; nonradiative recombination; passivation; spacer cations; surface dipole; surface treatment; wide band-gap perovskite